The protection of sunken WWII warships located in Indonesian or Malaysian territorial waters. (March 2020) - Lin, Zhen
Abstract: During the past five years, the sunken WWII warships in the territorial sea of Malaysia and Indonesia have fallen victim to large-scale illegal scavenging for scrap steel and low-background metal. At international level, the existing rules could not guarantee the protection of such shipwrecks. The laws and policies of the States in whose waters the shipwrecks are found are not adequate either. In addition, as the coastal States concerned generally lack the capacity to protect such shipwrecks, bilateral arrangements have to be made immediately. In the long run, joint efforts at regional level are necessary to combat the regional criminal network behind the illegal scavenging. Highlights: Illegal scavenging is destroying the sunken WWII warships in the South China Sea. International law has a limited effect on the protection of wrecks of WWII warships. The laws and policies of the coastal States are not adequate to protect these wrecks. Bilateral arrangements must be made immediately by the coastal States and flag States. Regional cooperation is needed to combat the criminal network behind the scavenging.